2018
DOI: 10.3390/w10040418
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Sb(III) and Sb(V) by Ferric Chloride Coagulation: Implications of Fe Solubility

Abstract: Coagulation and precipitation appear to be the most efficient and economical methods for the removal of antimony from aqueous solution. In this study, antimony removal from synthetic water and Fe solubility with ferric chloride (FC) coagulation has been investigated. The effects of pH, FC dosage, initial antimony loading and mixed Sb(III), Sb(V) proportions on Fe solubility and antimony removal were studied. The results showed that the Sb(III) removal efficiency increased with the increase of solution pH parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 50 publications
(100 reference statements)
12
49
0
Order By: Relevance
“…Moreover, Sb(III) demonstrated strong adsorption potential irrespective of pH in the presence of coexisting As and Sb species [36]. Our previous study [13] has shown the significant inhibition of Sb removal under coexisting Sb(III, V) conditions with higher Sb(V) fraction using FC coagulation. The higher adsorption capacity of poorly crystalline coagulant has been also reported [34].…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Moreover, Sb(III) demonstrated strong adsorption potential irrespective of pH in the presence of coexisting As and Sb species [36]. Our previous study [13] has shown the significant inhibition of Sb removal under coexisting Sb(III, V) conditions with higher Sb(V) fraction using FC coagulation. The higher adsorption capacity of poorly crystalline coagulant has been also reported [34].…”
Section: Introductionmentioning
confidence: 83%
“…The coagulation experiments were conducted to study the effect of pH (4-10) on Fe solubility and As, Sb removal, where 0.1 mM (27.029 mg/L) FC dose was used for solutions with 1 mg/L As(III, V) and Sb(III, V), respectively [13]. The experiments were also performed to study the competitive interactions of either As and Sb species in various binary systems over a broad pH range, where solutions contain single As and Sb species.…”
Section: Experimental Conditionsmentioning
confidence: 99%
See 3 more Smart Citations